Dictyostelium: A Model for Studying the Extracellular Vesicle Messengers Involved in Human Health and Disease - Irène Tatischeff (Cells, 2019)
Cell-derived extracellular vesicles (EVs) are newly uncovered messengers for intercellular communication. They are released by almost all cell types in the three kingdoms, Archeabacteria, Bacteria and Eukaryotes. They are known to mediate important biological functions and to be increasingly involved in cell physiology and in many human diseases, especially in oncology. The aim of this review is to recapitulate the current knowledge about EVs and to summarize our pioneering work about Dictyostelium discoideum EVs. However, many challenges remain unsolved in the EV research field, before any EV application for theranostics (diagnosis, prognosis, and therapy) of human cancers, can be efficiently implemented in the clinics. Dictyostelium might be an outstanding eukaryotic cell model for deciphering the utmost challenging problem of EV heterogeneity, and for unraveling the still mostly unknown mechanisms of their specific functions as mediators of intercellular communication.